Halaqas, relational subjects, and revolutionary committees in Syria - Al-Khalili, Charlotte (Focaal, 2021)
Through an ethnographic account of Syrian halaqas (Sunni religious circles) from the 1980s until the 2011 Syrian revolution, this article argues that halaqas have a revolutionary potential. The analysis demonstrates that Syrian religious circles are spaces of self-transformation that have heterotopic qualities. The Darayya halaqa studied here is a space where present and future are collapsed: a space in which future revolutionary selves and societies are already enacted. This temporal collapse is thus simultaneously a scalar one, for through the emergence of a relational or unbounded subject, a revolutionary project is being performed. This project is, moreover, without a preexisting program that its members seek to implement in a distant future; it is rather a revolutionary project that is perpetually in the making through discussions and actions happening within it.